Factores que influyen en la producción de quinua orgánica en el Distrito de San Jerónimo, Apurímac - Yauris Quispe, Nelida (2022)
Socioeconomic factors that influence the adoption of the organic system have received greater attention in the literature, however, the effect of motivational or socio-psychological factors of farmers has been analyzed to a lesser extent. To identify the socioeconomic, spatial, and motivational factors influencing the organic adoption of quinoa, the study area was focused on the district of San Jerónimo, Apurímac, which was chosen because it’s an area where quinoa production has increased with great notoriety, going from 3.1% (2011) to 11.9% (2020) of the national production of quinoa (MIDAGRI, 2021a), then 109 structured surveys were applied to quinoa producers. Finally, for the analysis of the information, descriptive statistics, correlation, and the Logit model were used. The results show that organic quinoa producers are motivated or attracted by financial reasons, followed by sustainability and obtaining healthy food free of pesticides. Also, the variables; Quinoa income, distance to the land, belonging to an association, technical assistance, and labor have an inverse relationship with crop organic adoption (with a significance level of less than 5%). While land ownership has a positive effect with a significance level of 10%.